2015
DOI: 10.1039/c4cc08735f
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped carbon dots decorated on graphene: a novel all-carbon hybrid electrocatalyst for enhanced oxygen reduction reaction

Abstract: An all-carbon hybrid, composed of coal-based nitrogen-doped carbon dots decorated on graphene, was prepared via hydrothermal treatment. The hybrid possesses comparable electrocatalytic activity, better durability and methanol tolerance than those of the commercial Pt-based electrocatalysts for oxygen reduction reaction, indicative of its great potential in fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(70 citation statements)
references
References 24 publications
(2 reference statements)
1
69
0
Order By: Relevance
“…Recently, non‐metal carbon‐based electrocatalysts have attracted great attention because of their excellent stability, low cost, and good methanol tolerance compared with Pt‐based catalysts . In particular, N‐doped CQDs have been widely used in the oxygen reduction reaction (ORR) as the catalyst or cocatalyst . The electrocatalytic activity of the prepared CQDs was evaluated by cyclic voltammetry (CV) by using a conventional three‐electrode system and linear sweep voltammetry (LSV) using a rotating disk electrode (RDE).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, non‐metal carbon‐based electrocatalysts have attracted great attention because of their excellent stability, low cost, and good methanol tolerance compared with Pt‐based catalysts . In particular, N‐doped CQDs have been widely used in the oxygen reduction reaction (ORR) as the catalyst or cocatalyst . The electrocatalytic activity of the prepared CQDs was evaluated by cyclic voltammetry (CV) by using a conventional three‐electrode system and linear sweep voltammetry (LSV) using a rotating disk electrode (RDE).…”
Section: Resultsmentioning
confidence: 99%
“…[2,57] In particular, N-doped CQDs have been widely used in the oxygen reduction reaction (ORR) as the catalysto r cocatalyst. [58] The electrocatalytic activity of the prepared CQDs was evaluated by cyclic voltammetry (CV) by using ac onventional three-electrode system andl inear sweep voltammetry (LSV) using ar otating disk electrode (RDE). As shown in Figure 7a,t he CQDs have ar eduction peak near À0.42 V. Moreover,i tc an be seen from Figure S10 (in the SupportingI nformation) that the dissolvedO 2 catalyzed by CQDs is asecondary reduction reaction, and the electron transfer number (n)o ft he CQDs is 1.33-1.38, indicating that the ORR activities of individual CQDsare relatively poor.T oimprove its catalysis properties, we chose to combine CQDs with graphene oxide (GO), called GO-CQDs.…”
Section: Resultsmentioning
confidence: 99%
“…35 In fact, carbon dots have emerged to represent now a rapidly advancing and expanding research field, as reflected by the large number of recent publications in the literature, with extensive investigations looking into many aspects of carbon dots for both fundamental and technological purposes. 316 …”
Section: Introductionmentioning
confidence: 99%
“…Carbon quantum dots (CQDs), nano-sized carbon particles, have attracted growing interest due to their high photochemical stability, low toxicity, good biocompatibility, and low environmental impact [18,19]. It has also been demonstrated that CQDs are of great potential in energy storage and conversions [20][21][22]. It is well known that there are abundant negative charged oxygen-containing functional groups on the surface of CQDs.…”
mentioning
confidence: 99%